Creative cartooning - Van De Vall, Tim (Artist's library series, 2014)
"With its contemporary approach, Creative Cartooning is the perfect guide to help yo get started in this popular art form. Inside you'll find everything you need to know to create dynamic characters, render gestures, and add props and costumes. You'll also find a helpful list and overview of basic tools and materials"--Page [4] of cover.